Angiotensin II induces a complex activation of transcription factors in the rat brain: expression of Fos, Jun and Krox proteins - LeBrun, C. J.; Blume, Annegret; Herdegen, Thomas; Seifert, Karin; Bravo, R.; Unger, T. (Neuroscience, 1995)
We investigated the effects of intracerebroventricular injection of angiotensin II on neuronal immediate early gene-encoded protein synthesis in the brain of conscious rats. The expression of seven immediate early gene-encoded transcription factors (c-Fos, FosB, c-Jun, JunB, JunD, Krox-20 (Engr-2) and Krox-24 (NGFI-A, Egr-1, Zif/268) was assessed simultaneously. Angiotensin II (1, 10, 100 ng) induced a dose-dependent expression of c-Fos and Krox-24 in the subfornical organ, the median preoptic area and in the paraventricular nucleus and supraoptic nucleus of the hypothalamus, regions known to be involved in the central osmoregulatory and neuroendocrine actions of angiotensin II. FosB expression was induced four hours after icv injection of the highest dose of angiotensin II in the median preoptic area and paraventricular nucleus; c-Jun expression was restricted to the median preoptic area, subfornical organ and paraventricular nucleus, and JunB was only induced in the median preoptic area and subfornical organ. In these above mentioned regions, JunD exhibited a high basal staining, which was not visibly altered by angiotensin II. Krox-20 was not induced by angiotensin II. Intracerebroventricular injections of isotonic saline did not induce immediate early gene expression in any of the above brain areas. The angiotensin II-AT1 receptor antagonist, losartan, applied intracerebroventricular five minutes prior to angiotensin II, prevented the angiotensin II-induced immediate early gene protein expression. Losartan alone had no effects on immediate early gene expression. Our data show for the first time that stimulation of central periventricular angiotensin II-AT1 receptors induces a finely tuned temporospatial expression of various immediate early gene-encoded transcription factors in distinct regions of the forebrain involved in blood pressure regulation and body fluid homeostasis. Thus, angiotensin II, in addition to its short-term regulatory actions, can participate through these transcription factors in neuroplastic processes.
Elektronische Reproduktion der Druck-Ausgabe 6. April 2000
Gesehen am 18.08.2025